Inhibitory effect of magnetic Fe3O4 nanoparticles coloaded with homoharringtonine on human leukemia cells in vivo and in vitro - Chen M (Dove Medical Press, 2016)
Meiyu Chen,1–3,* Fei Xiong,4,5,* Liang Ma,1–3,* Hong Yao,1–3 Qinrong Wang,1–3 Lijun Wen,1–3 Qian Wang,1–3 Ning Gu,4,5 Suning Chen1–3 1Jiangsu Institute of Hematology, The First Affiliated Hospital of Soochow University, Suzhou, 2Key Laboratory of Thrombosis and Hemostasis of Ministry of Health, Collaborative Innovation Center of Hematology, Soochow University, Suzhou, 3Collaborative Innovation Center of Hematology, Soochow University, Suzhou, 4State Key Laboratory of Bioelectronics, Jiangsu Key Laboratory for Biomaterials and Devices, School of Biological Science and Medical Engineering, Southeast University, Nanjing, 5Collaborative Innovation Center of Suzhou Nano Science and Technology, Suzhou, People’s Republic of China *These authors contributed equally to this work Abstract: Homoharringtonine (HHT), a natural cephalotaxine alkaloid, has been used in the People’s Republic of China for treatment of leukemia for >3 decades. Here, we employed magnetic Fe3O4 nanoparticles (MNP-Fe3O4) to improve the therapeutic effect of HHT and investigated its biological effects. Within a certain range of concentrations, the HHT-MNP-Fe3O4 showed a more enhanced inhibitory effect on the selected myeloid leukemia cell lines than HHT alone. Compared with HHT, HHT-MNP-Fe3O4 could induce more extensive apoptosis in leukemia cells, which also showed more pronounced cell arrests at G0/G1 phase. HHT-MNP-Fe3O4 enhanced antitumor activity by downregulating myeloid cell leukemia-1, which could inhibit the activation of caspase-3 and poly-ADP-ribose polymerase. In vivo experiments using tumor-bearing animal models showed that the mean tumor volume with HHT-MNP-Fe3O4 was significantly smaller than that with HHT alone (193±26 mm3 versus 457±100 mm3, P<0.05), while the mean weight was 0.67±0.03 g versus 1.42±0.56 g (P<0.05). Immunohistochemical study showed fewer myeloid cell leukemia-1-stained cells in mice treated with HHT-MNP-Fe3O4 than with the controls. These findings provide a more efficient delivery system for HHT in the treatment of hematological malignancy. Keywords: leukemia, magnetic nanoparticles, magnetic Fe3O4 nanoparticles, HHT